1983
DOI: 10.1111/j.1432-1033.1983.tb07642.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside biosynthesis in rat liver. Characterization of UDPgalactose- glucosylceramide galactosyltransferase and UDPgalactose-GM2 galactosyltransferase

Abstract: The conditions for the quantitative determination of UDP-Gal :glucosylceramide galactosyltrai~sferase and of UDP-Gal : GM, galactosyltransferase in Golgi-enriched preparations of rat liver were optimized. Triton X-100 was the detergent routinely used as octyl glucoside acted as a galactose acceptor forming octyl lactoside. Manganese ions were required for full activity, but Co2+ and Mg2+ could substitute to some extent. The nucleotide pyrophosphatase activity of the Golgi preparations which interfered with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…That this is not true was shown by MorrC and associates Keenan, 1974;Wilkinson et al, 19761, who, while studying with rat liver and cow mammary gland, found that the glycosphingolipid glycosyltransferases, the enzymes that synthesize the gangliosides, were mainly localized in the Golgi apparatus, where the enzyme enrichments were up to 50 times more over the starting homogenate; the plasma membrane preparation of the respective tissues, on the other hand, had very little of these enzyme activities. Many subsequent studies have established this, and almost all the glycosyltransferases of the rat liver Golgi apparatus have been studied and partially characterized [Wilkinson et al, 1976;Richardson et al, 1977;Eppler et al, 1980;Senn et al, 1981Senn et al, , 1983Kaplan and Hechtman, 19831. It is now believed that the gangliosides, after being synthesized in the Golgi apparatus, are transported to the plasma membrane, from where they reach the lysosomes for breakdown by the degrading enzymes.…”
Section: Introductionmentioning
confidence: 97%
“…That this is not true was shown by MorrC and associates Keenan, 1974;Wilkinson et al, 19761, who, while studying with rat liver and cow mammary gland, found that the glycosphingolipid glycosyltransferases, the enzymes that synthesize the gangliosides, were mainly localized in the Golgi apparatus, where the enzyme enrichments were up to 50 times more over the starting homogenate; the plasma membrane preparation of the respective tissues, on the other hand, had very little of these enzyme activities. Many subsequent studies have established this, and almost all the glycosyltransferases of the rat liver Golgi apparatus have been studied and partially characterized [Wilkinson et al, 1976;Richardson et al, 1977;Eppler et al, 1980;Senn et al, 1981Senn et al, , 1983Kaplan and Hechtman, 19831. It is now believed that the gangliosides, after being synthesized in the Golgi apparatus, are transported to the plasma membrane, from where they reach the lysosomes for breakdown by the degrading enzymes.…”
Section: Introductionmentioning
confidence: 97%
“…After its first discovery in the nervous system (Basu et al, 1968) and in the rat spleen (Hildebrand & Hauser, 1969), it was reported in other tissues such as bone marrow (Taki et al, 1982) and renal cells (Chatterjee & Castiglione, 1987). In rat liver, the presence of GalT-2 was suggested (Senn et al, 1983), but exogenous GlcCer-dependent formation of true LacCer could not be demonstrated in vitro (Walter et al, 1983). In vivo, the occurrence of glycosylation of exogenous GlcCer (Trinchera et al, 1990b) suggests that GalT-2 fThis work was supporlcd by a grant from the Ministero della Pubblica Islruzione, Rome (Grant MPI 1989, 60%).…”
mentioning
confidence: 99%
“…11). These reactions are catalyzed by specific glycosyltransferases, many of which were studied and partially characterized in rat liver Golgi apparatus (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Most major mammalian gangliosides derive from the a or b series (22).…”
mentioning
confidence: 99%